Consequences of Providing Nursing Care in the Neonatal Intensive Care Unit - (:unkn) unknown (My University, 2015)
Compassion fatigue is a negative consequence of providing nursing care. It impacts nurses physically, emotionally, and psychologically. The purpose of this cross-sectional study was to examine a model of negative consequences of providing nursing care including compassion fatigue, secondary traumatic stress, and burnout in the Neonatal Intensive Care Unit (NICU). The conceptual model of consequences of providing nursing care was identified, and then specifically applied to NICU nurses for this study. The conceptual model consists of five main concepts: patient factor, personal factor, work environment factor, positive consequences of providing nursing care, and negative consequences of providing nursing care. The research question of the current study was how the personal factor (e.g., age, years of nursing experiences, self-compassion) and the work environment factor (e.g., nursing foundations for quality of care, collegial nurse-physician relations, single family room NICU) influence the relationship between the patient factor (i.e., intensity and frequency of contact with the infant and family, clinical characteristics of the infant) and negative consequences of providing nursing care. It was hypothesized that the indirect effect of self-compassion in the relationship between the patient factor and negative consequences of providing nursing care would differ depending on levels of the personal factor or the work environment factor. Data were collected from 174 registered nurses who were 18 years of age or older and direct care providers in the staff position in NICUs in Wisconsin using an online survey. The online survey consisted of nine questionnaires which assessed demographics, personal and professional characteristics, personal experiences, clinical nursing experiences, perceptions regarding the working environment, feelings, and attitudes related to nursing care. A series of moderated mediation analyses were conducted using a different combination of independent variables (components of the patient factor) and moderators (components of the personal or the work environment factor) in each analysis. Out of 16 analyses, 5 analyses indicated significant results: the indirect effect of self-compassion in the relationship between the frequency of working 13 hours or more at stretch and negative consequences of providing nursing care was moderated by nursing foundations for quality of care and single family room NICU; the indirect effect of self-compassion in the relationship between the strength of the nurse-infant/family relationship and negative consequences was moderated by nursing foundations for quality of care and collegial nurse-physician relations; and the indirect effect of self-compassion in the relationship between the number of days that the nurse cared for the infant and negative consequences was moderated by collegial nurse-physician relations. The findings revealed important aspects that might reduce negative consequences of providing nursing care in the NICU: high level of nursing foundations for quality of care, positive collegial nurse-physician relations, single family room NICU, high level of self-compassion, decreased the intensity of contact with the infant and family, increased the frequency of contact with the infant and family, and strong nurse-infant/family relationship. In this exploratory study, the data supported several elements of the model of negative consequences of providing nursing care in the NICU. It provided an initial important step to understanding a mechanism of negative consequences of providing nursing care in the NICU. The study results may inform the development of interventions for negative consequences of providing nursing care at the individual level, the unit level, or the organizational level. Additional research is needed to examine other relevant factors of consequences of providing care to obtain empirical data to further test the model. In addition, studies in other nursing specialties are necessary to develop the nursing knowledge of compassion fatigue and other negative consequences of providing care.
Keywords: Burnout; Compassion Fatigue; Neonatal Intensive Care Unit; Nurses; Secondary Traumatic Stress